Rhyming Techniques and Identity in Korean Hip Hop - Park, Jinny (Journal of World Popular Music, 2021)
This article examines the development of Korean rhyming techniques by musically analysing phonetic and grammatical structure in Korean rap. Due to major differences between Korean and English, Korean MCs had to redefine what constitutes “rhyme” in Korean rap, and the conflicting definitions of what it means to rhyme in Korean reflect diverse identities in the Korean hip hop community. Through my musical analyses, I present five types of Korean rhyming techniques: flexible word order, artificial stress accents or artificial pitch accents, rhythmic motives, multisyllabic internal rhymes and translingual rhymes. I close the article by suggesting that there is an inevitable hybridity in Korean hip hop and socioeconomic class struggles that persists in Korea.